Authentication of Middle East Mandi Rice at “Cafe Zamrud” Restaurant - Fadzan Rahmidi; Atat Siti Nurani; Karpin Karpin (Media Pendidikan Gizi dan Kuliner, 2023)
This research is motivated by the popularity of the Middle East Mandi Rice dish in the city of Jakarta. Mandi Rice is a typical rice dish from Hadramaut, Yemen which is unique in terms of the use of ingredients, herbs, spices, tools, processing and presentation. This aspect makes it authentic and differentiates Mandi Rice from other Middle Eastern rice dishes. One of the restaurants in the city of Jakarta that serves Mandi Rice is the ”Cafe Zamrud” restaurant. The making of Mandi Rice at the “Cafe Zamrud” restaurant is not necessarily done in an authentic way as is done by the people in their area of origin. The purpose of this study was to determine authentication related to ingredients, seasonings, tools, processing and serving of Mandi Rice at the "Cafe Zamrud" restaurant. The author uses a qualitative approach with the case study method and uses triangulation techniques, namely observation, interviews and documentation in collecting data. Participants were taken by purposive sampling technique, with restaurant owners, cooks and servers as the participants. The research findings show that there are significant differences in the aspects of the use of spices, tools and processing of Mandi Rice dishes at the "Cafe Zamrud" restaurant with the aspects of authentic Mandi Rice dishes. There is also a slight difference in the aspect of the main meat ingredients and seasonings used in the "Cafe Zamrud" restaurant. Overall, it is known that the Mandi Rice dish served at the “Cafe Zamrud” restaurant is not an authentic Mandi Rice. The conclusion of this research is that Mandi Rice in the restaurant "Cafe Zamrud" is not an authentic Mandi Rice dish because there are several aspects that are not in accordance with the rules regarding Authentic Mandi Rice dishes.